Therapeutic Potential of Cannabinoids in Glaucoma – Hit or Myth? - A Review - Julia Górny; Alicja Kapciak; Tomasz Forenc; Jonasz Jurek; Aleksandra Pelczarska; Jaromir Hunia; Marcin Komorowski; Rafał Kaczorowski; Michał Janiszewski (Quality in Sport)
Introduction: Glaucoma is a leading cause of irreversible blindness, characterized by elevated intraocular pressure (IOP) that damages the optic nerve. Current treatments mainly focus on reducing IOP, but some patients do not respond adequately to conventional therapies. Cannabinoids, particularly Δ9-tetrahydrocannabinol (Δ9-THC), have been investigated as potential adjunctive treatments for glaucoma. Studies have shown varying effects of cannabinoids on IOP regulation, though their precise mechanisms remain unclear.